Effect of alum sludge on concrete strength and two way shear capacity of flat slabs. (June 2022) - Ahmed, Faris R.; Muhammad, Muhammad A.; Ibrahim, Rahel K.
Abstract: Alum sludge (AS) generated from water treatment plants as a byproduct waste is increasingly becoming a significant issue with the growing world population and high demand for drinking water. Alum sludge waste management needs an economically and environmentally effective solution instead of landfilling in the world. This paper experimentally studied the influence of AS content, from Taq Taq water treatment plant in the Kurdistan region of Iraq, on the density and compressive strength of concrete made of 0, 5, 10, 15, and 20% cement replacement by mass. The water/ binder ratio was kept constant at 0.45. The possibility of AS reuse in concrete slab structures tested for two way shear was investigated as well. Five different mixtures were made, and ten slab panels (2 for each mix) were cast. The slab panels (500x500x50) mm with different recess depths were simply supported and tested under concentrated column load. The results showed a slight reduction in density and compressive strength with increasing AS content at the curing age of 7 and 28 days. Also, Failure mode, load–deflection response, punching perimeter, shear load, shear strength, and ductility of tested slab panels containing AS are discussed and compared with international codes. It can be concluded that both recess depth and AS contents affect the two way shear behaviors. The results of experimental shear strength for tested slabs showed better performance up to 5% alum sludge.